Understanding the Key Factors Influencing Cybersecurity Practices in Nepalese Organizations (OCEM Journal of Management, Technology & Social Sciences, 2025)
This study investigates the critical factors affecting cybersecurity in Nepal, focusing on understanding the socio-economic, cultural, organizational, and technological challenges various sectors face. As Nepal undergoes rapid digital transformation, adopting online services like e-commerce, banking, and education has escalated the risk of cyber threats. Despite some progress in cybersecurity awareness and policy development, Nepal's cybersecurity practices are still underdeveloped, particularly within government institutions, small businesses, and sectors like healthcare and education. The research identifies key barriers to effective cybersecurity, including insufficient resources, lack of skilled personnel, and limited technological infrastructure.The study employs a quantitative research design, using a sample of 251 organizations across multiple sectors. Data were collected through structured questionnaires, assessing organizational characteristics, socio-economic factors, and cybersecurity practices. Statistical methods, including Principal Component Analysis (PCA) and binary logistic regression, were used to analyze the data, revealing that organizational support, resources, and leadership significantly impact cybersecurity practices. However, the study highlights a gap in research on the specific socio-economic and technological factors influencing cybersecurity in Nepal's rapidly expanding digital economy.Findings suggest that while private organizations demonstrate higher cybersecurity awareness than public institutions, small and medium enterprises (SMEs) are particularly vulnerable due to financial and technical constraints. The study highlights the need for context-specific cybersecurity solutions tailored to Nepal's unique socio-economic and institutional landscape. By addressing these challenges, the research aims to inform policymakers, businesses, and educational institutions to strengthen cybersecurity resilience in Nepal.